The History of Sindh from Islamic Conquests to the Arrival of the Conqueror of Sindh: An Analytical Study - Zabih ur Rahman; Nawaz, Rab (Journal of Islamic and Religious Studies, 2020)
According to the Islamic historical sources, the first voyages of Arab Muslims towards Sindh started during the caliphate period of Hazrat Umar. However, in the historical records, the 77-year-long struggle period of Muslims for conquest and Islamization was neglected until the arrival of Muḥammad bin Qasim. In this article, an analytical study is made about the history of the first period of the arrival and spread of Islam in Sindh from the beginning of the Islamic conquests up to the arrival of the conqueror of Sindh. The study also highlights the geographical identification of the Sindh region and the arrival of the companions of the Prophet (PBUH) and their expedition activities in Sindh. Besides that, the political situation of the Muslims in the Sindh region is discussed as well. The study concludes that before the arrival of Muḥammad bin Qasim, the first phase of Sindh's conquests and Islamization was completed by the extraordinary efforts of the companions of Prophet (PBUH) and Muslim commanders who were sent to the Sindh region. Eventually, this first phase turned out to be an important milestone in the subsequent conquests of Islam.